Standard precaution and incidence of needle stick injury during children vaccination among nurses working in maternal and child health centers in El-Minia governorate - Hossein, Yosria (International Journal of Advanced Nursing Studies, 2014)
Background: Persons administering vaccines should follow necessary precautions to minimize risk for spreading disease. Nurses have a significant role in this process and are responsible for implementing several infection control strategies. Syringes and needles used for injections must be sterile and disposable to minimize the risk of contamination. The Centers for disease Control and prevention (CDC) estimates that each year 384,000 needle sticks injuries (NSI) and other sharp – related percutaneous injuries are sustained by hospital – based healthcare personnel, an average of over 1,000 sharp injuries per day. The estimate is not including other health care settings, such as emergency services, outpatient Clinics home based care and nursing homes.Objective: This study aims to identify the standard precaution and the Incidence of Needle Stick Injury Among nurses working in Maternal and Child Health Centers during Children vaccination in El-Minia GovernorateMaterial and Method: Cross sectional study was utilized to meet the aim of the study, this study was conducted in the ten(10) minister center of health (MCH) at EL- Minia from May to August 2012, the Nurses participated in this study included (100) Nurses who are working in (M CH) center after receiving their consents for participation. Observation checklist was done to observe the nurses performance before, during and after child vaccine and procedure toward universal precaution.Results: that the highest frequency of nurses were in the age intervals 30<40 years with main age (34.3 ± 9.4) all sample were females and secondary school degree in nursing. More than have of them 55%were having 10:20 years of experience in nursing, Relation between nurse's incidences of needle stick injury and their experience, show statistically significant differences. Also the relation between nurse's incidences of need stick injury and their training, were good with statistically significant differencesConclusion: The study showed a high prevalence of needle stick injuries and low of using standard precaution among nurses during vaccination the child so suggests that every MCH must have an infection control committee for observation the using of standard precaution and training the nurses for prevention of needle stick injury.